2020
DOI: 10.1021/acs.joc.9b02083
|View full text |Cite
|
Sign up to set email alerts
|

Solid-Phase Synthesis of Hybrid 2,5-Diketopiperazines Using Acylhydrazide, Carbazate, Semicarbazide, Amino Acid, and Primary Amine Submonomers

Abstract: We report the solid-phase synthesis of N,N′-di­(acylamino)-2,5-diketopiperazine, an acylhydrazide-based conformationally rigid 2,5-DKP scaffold having exocyclic N–N bonds. We also show that different combinations of acylhydrazides, carbazates, semicarbazides, amino acids, and primary amines can be used to synthesize a highly diverse collection of hybrid DKP molecules via the solid-phase submonomer synthesis route. Finally, we show incorporation of a methyl substituent in one of the carbon atoms of the DKP ring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…To incorporate backbone chirality, we synthesized chiral azapeptoid monomers 19 – 23 (Figure 3) by following a method previously developed in our group [64] . 1 H and 2D‐NOESY NMR studies showed the presence of only the trans amide isomer of 19 – 23 in CDCl 3 and C 6 D 6 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To incorporate backbone chirality, we synthesized chiral azapeptoid monomers 19 – 23 (Figure 3) by following a method previously developed in our group [64] . 1 H and 2D‐NOESY NMR studies showed the presence of only the trans amide isomer of 19 – 23 in CDCl 3 and C 6 D 6 .…”
Section: Resultsmentioning
confidence: 99%
“…To incorporate backbone chirality, we synthesized chiral azapeptoid monomers 19-23 (Figure 3) by following a method previously developed in our group. [64] 1 H and 2D-NOESY NMR studies showed the presence of only the trans amide isomer of 19-23 in CDCl 3 and C 6 D 6 . We could crystallize compounds 19 and 20, which also confirmed backbone trans amide geometries of these molecules.…”
Section: Effect Of Introduction Of Backbone Chirality On Azapeptoid C...mentioning
confidence: 95%
“…Solid-phase synthesis of CDPs [ 77 , 78 ] offers the possibility to rapidly gain access to a plethora of structurally complex products [ 79 ]. Solid-phase methods can be very convenient for the rapid screening of arrays of libraries obtained through the parallel synthesis of CDPs, for instance via the SPOT method on cellulose membranes ( Scheme 2 ) [ 80 ].…”
Section: Synthesis Of Cdpsmentioning
confidence: 99%